Unraveling the mysterious flowering cycles of Mexican Guadua species: A captivating natural phenomenon - María de la Luz Perez-Garcia; Eduardo Ruiz-Sanchez (Advances in Bamboo Science, 2023)
The flowering of woody bamboos has remained an enduring mystery over time. Woody bamboos can persist in a vegetative state for up to 150 years. Among these intriguing flowering bamboos are the Guadua species. Guadua, a Neotropical genus of woody bamboos, is native to the Americas and comprises 34 species. In Mexico, there are seven native species, and their flowering cycles continue to puzzle researchers. These species are primarily found in the southeastern part of the country, often along rivers and bodies of water. Presently, many of these species face threats from cattle grazing and agricultural activities, including sugarcane production. To unravel the mystery of Guadua species flowering, we conducted a thorough review of Mexico's primary herbaria and online records, complete with digital images. Through our investigation, we have identified a total of 69 flowering events spanning over a century of history for six out of the seven Guadua species in Mexico. Mexican Guadua species exhibit sporadic flowering patterns, with one species, Guadua paniculata, displaying gregarious mass flowering. Furthermore, four of the six species flower at intervals of 30–34 years. Understanding the reproductive biology of Guadua is of paramount importance for the long-term preservation of these species. Our research sheds light on one of nature's deepest secrets and underscores the critical significance of their conservation.